Adapting Agile Methodologies for Full-Stack Teams - Prathyusha Kosuru (North American Journal of Engineering Research, 2022)
The modern world of software development has been greatly influenced by the use of Agilemethodologies to enhance the flexibility of the teams. This article will therefore explain how Scrum andKanban should be implemented in teams that engage in full-stack development where both the client andserver-side work is done. Unlike Scrum, which uses small cycles called sprints to encourage iterativeprogress, Kanban focuses on continuous delivery and visualization of work. Full-stack developmentcovers both front-end and back-end; this way, teams can handle projects in a better way and also make iteasier to integrate. In order to achieve the goal of enhancing collaboration, this paper focuses on the keyaspects of creating collaboration, advantages and disadvantages of collaboration, and principles ofcreating collaboration for specific contexts.Moreover, it will also give the details about the need for a cross-functional approach to improve thespeed of delivery. Appropriate equipment can facilitate the work smoothly while the evaluation ofeffectiveness is crucial in order to maintain the velocities gained. Readers will be able to get moreinsights and ideas about the fact that agility indeed pays off through real-life examples of full-stack Agileimplementations (Andersson, 2022)